Impact of Reflective Assessment on Student Learning: Best-Evidence Synthesis from Ten Quantitative Studies - Bond, John; Denton, David W.; Ellis, Arthur (International Dialogues on Education Journal, 2015)
Formative assessment involves feedback to teachers for informing instruction and also feedback to students for directing their own learning. Early research on formative assessment showed independence from any particular theoretical foundation. Self-regulated learning theory provides a helpful construct for organizing formative assessment through familiar classroom practices, including provision of feedback, strategy use, and metacognition. One way to integrate reflective activities is with reflective assessment, which emphasizes gathering feedback through questioning, writing, and discussing. Ten studies were analyzed using best-evidence methodology to show the effects of reflective assessment on student performance of posttest and retention tests. Weighted mean effect sizes ranged from .28 to .37. Results suggest additional investigations into the use of reflection for improving student learning and other outcomes.